Initiative, Personality and Leadership in Pairs of Foraging Fish - Nakayama, Shinnosuke; Harcourt, Jennifer L.; Johnstone, Rufus A.; Manica, Andrea (PLOS ONE, 2012)
Studies of coordinated movement have found that, in many animal species, bolder individuals are more likely to initiate movement and shyer individuals to follow. Here, we show that in pairs of foraging stickleback fish, leadership is not merely a passive consequence of temperamental differences. Instead, the act of initiating a joint foraging trip out of cover itself brings about a change in the role that an individual plays throughout the subsequent trip, and success in recruiting a partner affects an individual's tendency to initiate the next trip. On each joint trip, whichever fish took the initiative in leading out of cover gains greater influence over its partner's behaviour, which persists even after several changes in position (i.e. termination attempts and re-joining). During any given trip, the initiator is less responsive to its partner's movements than during trips initiated by the partner. An individual's personality had an important effect on its response to failure to recruit a partner: while bold fish were unaffected by failures to initiate a joint trip, shy individuals were less likely to attempt another initiation after a failure. This difference provides a positive feedback mechanism that can partially stabilise social roles within the pair, but it is not strong enough to prevent occasional swaps, with individuals dynamically adjusting their responses to one another as they exchange roles.